2022
DOI: 10.1016/j.radcr.2021.11.003
|View full text |Cite|
|
Sign up to set email alerts
|

Metastatic rectal gastrointestinal stromal tumor with intestinal obstruction: A rare case report

Abstract: Gastrointestinal stromal tumors (GISTs) arising from the rectum are rare. We report the case of an aggressive rectal gastrointestinal stromal tumor (GIST) in a 60-year-old female that presented for symptoms of constipation and lower gastrointestinal bleeding. Upon rectal examination, a hard mass was found at 6cm from the anal marge. An MRI was indicated that shows a well-demarcated lesion originates from the distal rectum with exophytic growth and central necrosis. The diagnosis of rectal gist was confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…MRI has advantages in diagnosing hepatic metastasis; a previous study reported that MRI detected additional hepatic metastasis, which was not detected via CT [ 38 ]. Additionally, MRI enables detailed visualization of the pelvic anatomy, including the anal sphincter and anal verge, as well as the tumor itself [ 39 ].…”
Section: Imaging Modalitymentioning
confidence: 99%
“…MRI has advantages in diagnosing hepatic metastasis; a previous study reported that MRI detected additional hepatic metastasis, which was not detected via CT [ 38 ]. Additionally, MRI enables detailed visualization of the pelvic anatomy, including the anal sphincter and anal verge, as well as the tumor itself [ 39 ].…”
Section: Imaging Modalitymentioning
confidence: 99%